(3hGbY GdCef GdZPGFj GdYQHj heSJbHdgs - (3UHMj(B, (3GdbGSes ((3HjQhJ(B;(3YeGf(B,(3GdeDSSI GdYQHjI ddOQGSGJ h GdfTQ(B:s (3eDSSI YHO GdMejO TheGf(B,s, 2010)
(3eDTQGJ GdCef GdZPGFj GdYQHj , bVGjG YOO GdScGf h JCKjQg Ydi GdCef GdZPGFj , LOGhd GdScGf , Gdbhi GdYGedi aj GdRQGYI , eUGOQ GdeYdheGJ GdefThQI Yf Gdejdg aj GdOhd GdYQHjI , GdHMK GdYdej I GdJWhQ GdRQGYj aj GdOhd GdYQHjI , MOhd eDTQGJ GdGfaGb Ydi GdHMK GdYdej h GdJWhjQ , hGbY RQGYI GdeMGUjd GdRQGYjI (B: (3GdeSGMI h GdGfJGL h GdGfJGLjI aj GdMGVQ h GdeSJbHd , GfJGL GddMhe h GdGSeGc h GdMdjH , GdGfJGL h UGaj GdhGQOGJ ddehGQO GdZPGFjI GdQFjSI ceLehYI GdOhd GdYQHjI (B: (3MGVQgG h eSJbHdgG , LOGhd GfJGL GdeMGUjd dGge Ohd GdYGde hJWhQ GdCef GdZPGFj Ydi GdeSJhi GdhWfj ddOhd GdYQHjI , LOGhd eYOd cejI GdGfJGL h cejI bjeI UGaj GdhGQOGJ h GdcejI GdeJGMI ddGSJgdGc dcd OhdI YdI MOis
Keywords: (3GdCef GdZPGFjs; (3GdCef GdZPGFj(B- (3GdHdOGf GdYQHjIs; (3GdRQGYIs